Additional Notes on the Genus Lomatocarpa Pim. (Apiaceae - Apioideae) and Related Taxa of High Asia - Pimenov, M. G.; Kljuykov, E. V. (Rheedea, 2005)
Ligusticum wolffianum Fedde ex Wolff and Cortia schmidii Nasir described from North East Afghanistan and North Pakistan are determined to be identical with Lomatocarpa albomarginata (Schrenk) Pimenov & Lavrova, widely distributed  in the adjacent  Pamiro-Alai and Tianschan mountain systems. The species is known also from south-western extremity of Chinese autonomous region Xinjiang. A new combination (L. afghanica) has been proposed for the species, previously known as Ligusticum afghanicum, Lomatocarpa steineri, and Pachypleurum linearilobum.